Trade Liberalization, Foreign Direct Investment Liberalization, and Wage Inequality in Indonesia - Astriyany Astriyany; Shingo Takahashi (Pusat Penelitian, Badan Keahlian DPR RI, 2021)
This study purposes to re-examine the relationship between trade liberalization, foreign direct investment (FDI) liberalization, and wage inequality between unskilled and skilled workers by considering international trade theories, the Heckscher-Ohlin-Samuelson model, and The Human Capital theory from labor economics. The panel data sourced from the latest SAKERNAS or National Labor Force Survey of Indonesia between 2015 and 2017 are estimated to determine employment by gender, age, marital-status, wages per hour, level of education, and classification of industry. Wage inequality is examined by using a two-stage estimation strategy. Specifically, in the first stage, using SAKERNAS data at the household level, wages are regressed with their worker characteristics to get coefficients of our interest, which are industry wage premium for unskilled workers and industry wage premium for a skilled worker. In the second stage, in the industrial level, two sets of estimated coefficients are used as dependent variables and regressed with nominal tariff and FDI inflow as proxy variables to trade liberalization and FDI liberalization, respectively. Our estimation showed that trade liberalization and FDI liberalization do have a statistically significant relationship with industry wage premium for unskilled workers. In contrast, there is a positive relationship for the case of an industry wage premium for skilled workers. Overall, the results show that trade liberalization decreases wage inequality between unskilled and skilled workers, which in line with the HOS model. Moreover, FDI liberalization increases wages for skilled workers, which in line with Human Capital theory.Keywords: trade liberalization, FDI liberalization, wage inequalityAbstrakPenelitian ini bertujuan untuk mempelajari kembali hubungan antara liberalisasi perdagangan, liberalisasi penanaman modal asing (PMA), dan ketimpangan upah di Indonesia antara pekerja berkemampuan tinggi dan pekerja berkemampuan rendah dengan mempertimbangkan teori perdagangan internasional yaitu Heckscher-Ohlin-Samuelson model dan teori tenaga kerja yaitu teori Human Capital. Panel data berasal dari data terbaru survei angkatan kerja nasional (SAKERNAS) antara tahun 2015 dan 2017 yang digunakan untuk mengestimasi pekerja berdasarkan jenis kelamin, umur, status perkawinan, gaji per jam, tingkat pendidikan dan klasifikasi industri. Ketimpangan upah diukur menggunakan dua tahap metode estimasi. Di metode tahap pertama, dengan menggunakan data SAKERNAS di level individu, data upah diregresi menggunakan karakteristik pekerja untuk mendapatkan estimasi koefisien ketimpangan upah yang diinginkan yaitu untuk pekerja berkemampuan tinggi dan pekerja berkemampuan rendah. Di metode tahap kedua, hasil koefisien dari metode tahap pertama digunakan sebagai variabel terikat untuk kemudian diregresikan dengan nominal tarif sebagai proksi atau representasi dari liberalisasi perdagangan dan PMA inflow sebagai proksi dari liberalisasi PMA. Hasil penelitian ini mengindikasikan bahwa liberalisasi perdagangan dan liberalisasi PMA memiliki pengaruh yang signifikan terhadap ketimpangan upah untuk pekerja yang berkemampuan rendah, sedangkan untuk ketimpangan upah pekerja berkemampuan tinggi terdapat hubungan yang positif dan linier. Secara keseluruhan, hasil penelitian ini menunjukkan bahwa liberalisasi perdagangan menurunkan ketimpangan upah antara pekerja berkemampuan tinggi dan pekerja berkemampuan rendah yang linier dengan HOS model dan liberalisasi PMA menaikkan upah untuk pekerja berkemampuan tinggi yang linier dengan teori Human Capital.Kata kunci: liberalisasi perdagangan, liberalisasi PMA, ketimpangan upah